The Murder of Angela Mischelle Lawless: An Honest Sheriff and the Exoneration of an Innocent Man - Snodgrass, Stephen R. (Rowman & Littlefield Publishers, 2023)
In a small Missouri town in 1992, the body of 19-year-old Mischelle Lawless was found in her car, stalled on the side of a road. 18-year-old Josh Kezer was arrested and charged for her murder—even though he was in a different state at the time, as proven by witnesses—and spent the next 16 years of his life in prison. How was Josh imprisoned for a crime he didn’t commit? Author Stephen R. Snodgrass expertly unveils the web of manipulation and corruption that led to Josh’s conviction, everything that could go wrong in the American criminal justice system did, from snitch witnesses who were coached by law enforcement to lie, to withheld exculpatory evidence, and an unscrupulous prosecutor knowingly using false testimony that had been recanted. Kezer was convicted and served 16 years in violent Missouri prisons until a part-time deputy who was at the murder scene was elected Sheriff of Scott County and quietly reopened the investigation and has continued his quest to find the real killer. Snodgrass draws on interviews with Josh himself, the research of Sheriff Rick Walter, the first responder to the scene who later went on to exonerate Josh in a re-trial, and his own legal analysis, to reveal the truth behind the case, the conviction, and the exoneration. This book is a timely, compassionate work of true crime that calls for better and more equitable justice for all.